2015
DOI: 10.1001/jamaneurol.2015.1359
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Cerebral Microbleeds and Cerebral Blood Flow in Elderly Individuals

Abstract: IMPORTANCE Cerebral microbleeds (CMBs) are collections of blood breakdown products that are a common incidental finding in magnetic resonance imaging of elderly individuals. Cerebral microbleeds are associated with cognitive deficits, but the mechanism is unclear. Studies show that individuals with CMBs related to symptomatic cerebral amyloid angiopathy have abnormal vascular reactivity and cerebral blood flow (CBF), but, to our knowledge, abnormalities in cerebral blood flow have not been reported for health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…They also showed that the increased volume of WMLs as well as the presence of lacunar infarctions was not associated with an impaired vascular reactivity, which is consistent with our previous findings [16]. On the other hand, Gregg et al [25] reported that incidental CMBs in cortical locations, which were likely the result of cerebral amyloid angiopathy, were associated with widespread reductions in resting-state CBF in cognitively normal elderly individuals. In the present study, group II patients, whose CMBs were mainly located in both the lobar and deep brain areas, exhibited reduced CBF and preserved CMRO 2 in the centrum semiovale, the terminal regions supplied by deep perforating arteries.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They also showed that the increased volume of WMLs as well as the presence of lacunar infarctions was not associated with an impaired vascular reactivity, which is consistent with our previous findings [16]. On the other hand, Gregg et al [25] reported that incidental CMBs in cortical locations, which were likely the result of cerebral amyloid angiopathy, were associated with widespread reductions in resting-state CBF in cognitively normal elderly individuals. In the present study, group II patients, whose CMBs were mainly located in both the lobar and deep brain areas, exhibited reduced CBF and preserved CMRO 2 in the centrum semiovale, the terminal regions supplied by deep perforating arteries.…”
Section: Discussionsupporting
confidence: 87%
“…Although one patient in group I had a strictly lobar CMB, he had a history of long-lasting hypertension and dyslipidemia. The mean CBF value of the cortical-subcortical regions was 36.7 mL/100 g/min, and widespread reductions in the resting-state CBF as pointed out by Gregg et al [25] were not observed in this patient. As patients with subcortical CMBs could have microangiopathy related to lipohyalinotic changes instead of amyloid angiopathy in some cases [26,27], we considered that the CMB of that patient derived from hypertensive vasculopathy.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, in patients with ischemic stroke and/or transient ischemic attacks, lobar CMBs are associated with executive dysfunction[25]. Lobar CMBs are also associated with lower cerebral blood flow and hypoperfusion in both healthy elderly and in a memory clinic setting [26,27], which highlights the complex interaction of SVD with healthy ageing. Again, ApoE ε4 is associated with lobar CMBs in patients with cognitive impairment[28].…”
Section: Vascular Factors In Admentioning
confidence: 99%
“…Another similarly well-designed recent study showed a strong correlation between incidental CMBs in cortical locations and widespread reductions in resting-state cerebral blood flow of nondemented individuals with a mean age of 86.8. 42 The most plausible explanation is indeed CAA causing both cortical CMBs and also vascular dysfunction, the latter resulting in decreased perfusion. Not surprisingly, however, CMB(+) participants did not have a higher amyloid load than CMB(−) participants, probably because of confounding by fibrillary parenchymal plaques commonly found in this old cohort.…”
Section: Molecular Neuroimaging In Other Svd Cohortsmentioning
confidence: 99%